Interaction Between Prediabetes and the ABO Blood Types in Predicting Postsurgical Esophageal Squamous Cell Carcinoma-Specific Mortality: The FIESTA Study - Fan, Guohui; Hu, Dan; Zhang, Xinran; Peng, Feng; Lin, Xiandong; Chen, Gang; Liang, Binying; Zhang, Hejun; Xia, Yan; Zheng, Xiongwei; Jie, Jianzheng; Niu, Wenquan (Frontiers in Oncology, 2018)
Background: We aimed to investigate the interaction between prediabetes and the ABO blood types in predicting esophageal squamous cell carcinoma (ESCC)-specific mortality by analysing data from the FIESTA study on normal/prediabetic patients with ESCC. Methods: Total 1,857 normal/prediabetic patients with ESCC who underwent three-field lymphadenectomy between January 2000 and December 2010 and survived hospitalization were analyzable, with follow-up beginning in 2000 and ending in 2015. Results: At the end of the follow-up, there were 1,161 survivors and 696 non-survivors. The follow-up time ranged from 0.5 to 180 months. The cumulative survival rates in normal patients were obviously better than in prediabetic patients. The cumulative survival rates were significantly higher in normal patients than in prediabetic patients for the blood types O and A (Log-rank test P < 0.05), while no significance was detected for the blood types B and AB. Adjusted risk estimates for ESCC-specific mortality for prediabetic patients relative to normal patients were statistically significant in the blood type B− group (hazard ratio [HR]: 1.71; 95% confidence interval [CI]: 1.33–2.20; P < 0.001), but not in the blood type B+ group (HR: 1.12; 95% CI: 0.77–1.64; P = 0.5544). Conclusions: Our findings indicate that prediabetes can predict the significant risk of ESCC-specific mortality in Chinese Han patients with the blood types O and A.